Research of rheological properties improvement methods of coal-water fuel based on low-grade coal; MATEC Web of Conferences; Vol. 141 : Smart Grids 2017 - Zenkov A. G. Andrey Gennadievich; Larionov K. B. Kirill Borisovich; Yankovsky S. A. Stanislav Aleksandrovich; Lavrinenko S. V. Sergey Viktorovich (2017, 2017)
Title screen